Stages of Transition to International Financial Reporting Standards (IFRS) in Uzbekistan and its Sustainable Development (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The transition to International Financial Reporting Standards (IFRS) in Uzbekistan is a key initiative aimed at enhancing financial transparency, attracting foreign investment, and promoting sustainable economic growth. This article examines the main challenges, solutions, and expected benefits in IFRS adoption in Uzbekistan. It emphasizes the importance of regulatory reforms, education, and technological upgrades in facilitating this transition. The analysis underscores the potential of IFRS to improve Uzbekistan's integration into the global economy and its impact on sustainable development.